2022
DOI: 10.5194/tc-16-3517-2022
|View full text |Cite
|
Sign up to set email alerts
|

Automated avalanche mapping from SPOT 6/7 satellite imagery with deep learning: results, evaluation, potential and limitations

Abstract: Abstract. Spatially dense and continuous information on avalanche occurrences is crucial for numerous safety-related applications such as avalanche warning, hazard zoning, hazard mitigation measures, forestry, risk management and numerical simulations. This information is today still collected in a non-systematic way by observers in the field. Current research has explored the application of remote sensing technology to fill this information gap by providing spatially continuous information on avalanche occurr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
(46 reference statements)
2
18
0
Order By: Relevance
“…Code and data availability. The manually mapped avalanche outlines from 24 January 2018 and 16 January 2019 used by us for training, testing and validation are available on EnviDat (Hafner andBühler, 2019, 2021). The code is available on GitHub: https:// github.com/aval-e/DeepLab4Avalanches.git (last access: 22 August 2022) and Zenodo: https://doi.org/10.5281/zenodo.7014498 (Barton and Hafner, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Code and data availability. The manually mapped avalanche outlines from 24 January 2018 and 16 January 2019 used by us for training, testing and validation are available on EnviDat (Hafner andBühler, 2019, 2021). The code is available on GitHub: https:// github.com/aval-e/DeepLab4Avalanches.git (last access: 22 August 2022) and Zenodo: https://doi.org/10.5281/zenodo.7014498 (Barton and Hafner, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…5). The area contains avalanches in the shade and in illuminated terrain, as well as all outline quality classes in the initial mappings (Hafner andBühler, 2019, 2021). The mapping experts did not see another mapping before having finished theirs.…”
Section: Reproducibility Of Manually Mapped Avalanchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to automated detection, manual detection however is very time consuming and may often be subjective. Hafner et al (2022) conducted a study on the interobserver variability by comparing expert agreement on manual avalanche mapping in SPOT6/7 optical data. They found that the expert agreement is considerably lower than expected.…”
Section: Automated Detection Of Avalanches 221 Automated Detection Of...mentioning
confidence: 99%
“…In the recent study of Hafner et al (2022) an adapted DeepLabV3+, a state-of-the-art DL model, was applied to automatically detect and map avalanches in SPOT 6/7 satellite images from January 2018 and January 2019, which makes it the first attempt to apply a DL model to optical satellite data. For training, validation and testing of the model, a dataset comprising 24,778 manually annotated avalanche polygons was used.…”
Section: Automated Detection Of Avalanches 221 Automated Detection Of...mentioning
confidence: 99%